PPARγ ligands decrease hydrostatic pressure-induced platelet aggregation and proinflammatory activity. - Fang Rao; Ren-Qiang Yang; Xiao-Shu Chen; Jin-Song Xu; Hui-Min Fu; Hai Su; Ling Wang (PLoS ONE)
Hypertension is known to be associated with platelet overactivity, but the direct effects of hydrostatic pressure on platelet function remain unclear. The present study sought to investigate whether elevated hydrostatic pressure is responsible for platelet activation and to address the potential role of peroxisome proliferator-activated receptor-γ (PPARγ). We observed that hypertensive patients had significantly higher platelet volume and rate of ADP-induced platelets aggregation compared to the controls. In vitro, Primary human platelets were cultured under standard (0 mmHg) or increased (120, 180, 240 mmHg) hydrostatic pressure for 18 h. Exposure to elevated pressure was associated with morphological changes in platelets. Platelet aggregation and PAC-1 (the active confirmation of GPIIb/IIIa) binding were increased, CD40L was translocated from cytoplasm to the surface of platelet and soluble CD40L (sCD40L) was released into the medium in response to elevated hydrostatic pressure (180 and 240 mmHg). The PPARγ activity was up-regulated as the pressure was increased from 120 mmHg to 180 mmHg. Pressure-induced platelet aggregation, PAC-1 binding, and translocation and release of CD40L were all attenuated by the PPARγ agonist Thiazolidinediones (TZDs). These results demonstrate that platelet activation and aggregation are increased by exposure to elevated pressure and that PPARγ may modulate platelet activation induced by high hydrostatic pressure.